2013
DOI: 10.7555/jbr.27.20120076
|View full text |Cite
|
Sign up to set email alerts
|

Low dose bisphenol A impairs spermatogenesis by suppressing reproductive hormone production and promoting germ cell apoptosis in adult rats

Abstract: Bisphenol A (BPA), an estrogenic chemical, has been shown to reduce sperm count; however, the underlying mechanisms remain unknown. Herein, we show that oral administration of BPA (2 µg/kg) for consecutive 14 days in adult rats (BPA rats) significantly reduced the sperm count and the number of germ cells compared to controls. The serum levels of testosterone and follicle-stimulating hormone (FSH), as well as the level of GnRH mRNA in BPA rats were lower than those of control rats. Testosterone treatment could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(32 citation statements)
references
References 43 publications
1
30
0
1
Order By: Relevance
“…Other rodent studies suggest that BPA exposure can affect T production with one report suggesting developmental exposure to BPA increases this hormone [84], whereas other studies suggest this chemical decreases T production [85; 86; 87; 88; 89]. Similar to the BPA-analogue studies reported above, BPA can also affect sperm production and quality and increase sperm DNA damage in rodent models [90; 91; 92; 93; 94]. Some of the effects of BPAF and BPS in the CNS and other systems might be due to non-genomic actions [68; 69; 70].…”
Section: Neuroendocrine Disruption Due To Exposure Of Rodent Models Tmentioning
confidence: 77%
“…Other rodent studies suggest that BPA exposure can affect T production with one report suggesting developmental exposure to BPA increases this hormone [84], whereas other studies suggest this chemical decreases T production [85; 86; 87; 88; 89]. Similar to the BPA-analogue studies reported above, BPA can also affect sperm production and quality and increase sperm DNA damage in rodent models [90; 91; 92; 93; 94]. Some of the effects of BPAF and BPS in the CNS and other systems might be due to non-genomic actions [68; 69; 70].…”
Section: Neuroendocrine Disruption Due To Exposure Of Rodent Models Tmentioning
confidence: 77%
“…6B, E ). We decided to use a concentration of 0.05 µM of NP and BPA for the following experiments as this concentration was found to significantly increase the AP activity and is within the range of levels detected in human samples [28] , [30] , [53] , [54] . The AP activity started to increase in the culture medium as early as 1 h after treatment with 0.05 µM BPA or NP ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo study with adult rats suggests that low dosage (2 μg/kg body weight) of BPA after oral administration impairs spermatogenesis by reducing reproductive hormones to stop meiosis of germ cells and activating the Fas/FasL pathway to induce the apoptosis of germ cells, lowers the biosynthesis and secretion of testosterone via inhibiting the activity of GnRH neurons, and decreases the expression of steroidogenic enzymes. Subsequently, declining testosterone rate was accompanied by reduction of sperm concentration [90]. Another recent in vivo study with experimental rats evaluated the potential impact of BPA in the doses of 1, 5, 10 and 100 mg/kg body weight on spermatogenesis.…”
Section: Spermatogenesis and Sperm Function Affected By Bpamentioning
confidence: 99%